Photocatalytic activities of Fe-Cu/TiO2 on the mineralization of oxalic acid and formic acid under visible light irradiation - Apiwong-ngarm K. (Elsevier, 2014)
Pure TiO2 and (Fe,Cu)-codoped TiO2 nanoparticles with different nominal doping amounts of Fe and Cu in the range of 0.1-5.0mol% were synthesized by the modified sol-gel method. The samples were characterized in order to obtain the correlation between physicochemical properties and photocatalytic properties by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Brunauer, Emmett and Teller (BET) specific surface area, UV-vis diffuse reflectance spectroscopy (UV-vis DRS), X-ray photoelectron spectroscopy (XPS), zeta potential, and inductively coupled plasma (ICP) techniques. Photocatalytic activities of 0.1-5.0mol% (Fe,Cu)-codoped TiO2 on the mineralization of oxalic acid and formic acid under visible light irradiation were studied and the results were compared to pure TiO2 and commercial TiO2 (Degussa P25). The results clearly showed that 0.5mol% (Fe,Cu)-codoped TiO2 sample exhibited remarkably higher activity than pure TiO2. © 2014 Elsevier B.V.